Functional outcome of conservative and surgical management in mid-third clavicle fractures - Chandra Prakash Pal; Rajendra Kumar Shakunt; Deepak Kumar; Amrit Goyal; Aditya Prakash Tyagi; Trilok Chand Pippal (Journal of Orthopedics, Traumatology and Rehabilitation, 2015)
Purpose: Clavicle fracture traditionally treated conservatively. There is a growing trend to treat displaced mid-shaft clavicular fractures with primary open reduction and plate fixation; whether such treatment results in improved patient outcomes is debatable. The aim of this study was to compare union rates and functional outcomes for displaced mid-shaft clavicular fractures that were treated with either primary open reduction and plate fixation or nonoperative treatment. Material and Methods: In this prospective study, 32 patients between 18 and 60 years of age who had an acute displaced mid-shaft clavicular fracture were randomized to receive either primary open reduction and plate fixation (n = 12) or nonoperative treatment (n = 20). Functional assessment was conducted at 3 months, 6 months, and 1-year with the use of the constant scores. Union was evaluated clinically and radiographically. Complications were recorded and compared. Results: The rate of nonunion was significantly reduced after open reduction and plate fixation (none nonunion) as compared with nonoperative treatment (two nonunion). Constant scores were significantly better after open reduction and plate fixation than after nonoperative treatment; 93.7 versus 85.5. A major complication was found in 35% of patients in the conservative group while they were absent in operative group. Conclusions: Open reduction and plate fixation reduces the rate of nonunion after acute displaced mid-shaft clavicular fracture compared with nonoperative treatment and is associated with better functional outcomes. Open reduction and plate fixation using precontoured locking plate have low implant-related complications.